Calculate The Conductivity of Some Composites of Cellulose Bacteria Mixed with Polypyrol - Syukri Yunus; Hairul Abrar; Auliya Akbar (Jurusan Teknik Elektro Universitas Andalas, 2021)
The manufacture of composites that have good electrical properties is to use a conductive polymer matrix. A conductive polymer is a polymer compound that has a stable bond that allows the polymer to act as a good conductor of electricity. This study aims to determine the highest conductivity value of composite materials that have been coated with polypyrrole, namely bacterial cellulose with polypyrrole (bio composite 1), tempo bacteria cellulose with polypyrrole (bio composite 2), and Gambier bacteria cellulose with polypyrrole (bio composite 3). In this study, there were four samples consisting of nata de coco (cellulosic bacteria), 2, 2, 6, 6-tetramethylpiperidine 1-oxyl (TEMPO), Gambier extract, and polypyrrole. Measurement of resistance value using the two point probe method. The results of this study obtained that the resistance and conductivity values of bio composite 1, bio composite 2, and bio composite 3 were 29.742 kΩ and 1.178×10-3 S/cm, 20.338 kΩ and 1.692×10-3 S/cm, 34,572 kΩ and 0.9807×10-3 S/cm. The measurement results show that the highest conductivity value is bio composite 2.